Ultrastructure of abnormal membrane inclusions in nuclei of human myocardial cells. - Engedal, H (1977)
The ultrastructure of the nuclear envelope was studied in cardiac muscle cells of 12 patients undergoing cardiopulmonary bypass surgery. Two main types of membrane inclusions, globular and tubular, were observed in the nuclei. The globular type was found in 6 patients. The globular inclusions were about 0-5mu to 1-5mu in diameter and lined by two unit membranes equal in structure to that of the nuclear envelope. The lining was probably always in continuity with the nuclear membranes. Such inclusions contained a granular matrix in which no cytoplasmic organelles could be seen, with the exception of a limited number of ribosomes. The tubular type of nuclear inclusion was observed in the cardiac tissue of 3 patients. These tubules ran in straight or slightly bent segments of about 0-2 mu to 1-6 mu length, interrupted by bendings at obtuse or right angles. The diameter of their lumina measured about 300 A to 800 A. Such tubules were nearly always found in areas of the nucleoplasm rich in heterochromatin. Nuclear pore-like structures were occasionally found in the tubular wall. The tubular wall consisted of a single unit membrane shown to be in continuity with the inner membrane of the nuclear envelope. Since these nuclear aberrances have been observed at all of the stages examined, the possibility is considered that they may represent a specific nuclear response to the process of cardiac hypertrophy.